Pengaruh Penerimaan Pajak Daerah Terhadap Pendapatan Asli Daerah Di Provinsi Sumatera Utara - Agustina Pratiwi; Ardhansyah Putra Harahap (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the influence of regional tax revenues on the original regional income of North Sumatra province 2018-2022. This research uses a quantitative approach method with the type of data used in this research using secondary data obtained from target report data and realized income of the North Sumatra provincial government, data analysis used in this research using simple linear regression analysis, the population used in this research namely data on regional tax revenue reports and regional original income in North Sumatra province taken from the last 5 years starting from 2018-2022. The results of this research show that regional taxes have a significant effect on regional original income in North Sumatra province.